PENGARUH SELF EFFICACY DAN TOLERANCE FOR RISK TERHADAP MINAT ENTREPRENEURSHIP (STUDI PADA MAHASISWA MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS KHAIRUN) - Afniati, Afniati; W. Jabid, Abdullah (Jurnal MS, 2023)
ABSTRACT Objective: This research aims to determine the influence of product quality and price on purchasing decisions mediated by word of mouth in the case of the Puta Dino Tidore weaving house. Methodology: The population in this research is students from the Management Study Program, Faculty of Economics and Business, Khairun University class 2019-2021, totaling 547 people. The sampling technique used in this research is probability sampling, with a simple random sampling method so that the sample is 231 students. Findings: Partial hypotheses and simultaneous and partial hypotheses are accepted, because the alpha value is smaller than 5%. Conclusion: The results of the research show that self-efficacy has a positive and significant effect on the entrepreneurship interest of students in the Management Study Program, Faculty of Economics and Business, Khairun University, Ternate, which means that the higher the self-efficacy; and Tolerance for risk has a positive and significant influence on students' interest in entrepreneurship in the Management Departement, Faculty of Economics and Business, Khairun University, Ternate, which means that with tolerance for risk Â 